Response of peer relations and social activities to treatment with viloxazine extended‐release capsules (Qelbree®): A post hoc analysis of four randomized clinical trials of children and adolescents with attention‐deficit/hyperactivity disorder. Issue 4 (27th February 2023) - Faraone, Stephen V.; Gomeni, Roberto; Hull, Joseph T.; Busse, Gregory D.; Lujan, Brendan; Rubin, Jonathan; Nasser, Azmi
Abstract: Introduction: Attention‐deficit/hyperactivity disorder (ADHD) is associated with impairments related to peer relations (PR) and social activities (SA). The objective of this post hoc analysis was to assess the degree to which viloxazine extended‐release (viloxazine ER; viloxazine extended‐release capsules; Qelbree ® ) improves clinical assessments of PR and SA in children and adolescents with ADHD. Methods: Data were used from four Phase III placebo‐controlled trials of 100 to 600 mg/day of viloxazine ER ( N = 1354; 6–17 years of age). PR and SA were measured with the Peer Relations content scale of the Conners 3rd Edition Parent Short Form's Peer Relation content scale (C3PS‐PR) and the Social Activities domain of the Weiss Functional Impairment Rating Scale‐Parent Report's (WFIRS‐P‐SA) at baseline and end of study. ADHD symptoms were assessed weekly with the ADHD Rating Scale, 5th Edition. The analyses relied on the general linear mixed model with the subject as a random effect. Results: Improvement in C3PS‐PR ( p = .0035) and WFIRS‐P‐SA ( p = .0029) scores were significantly greater in subjects treated with viloxazine ER compared with placebo. When using measures of clinically meaningful response, the C3PS‐PR responder rate was significantly higher for viloxazine ER (19.2%) compared with placebo (14.1%) and the difference was statistically significant ( p = .0311); the Number Needed to Treat (NNT) was 19.6. The WFIRS‐P‐SA responder rate was significantly higher for viloxazine ER (43.2%) compared with placebo (28.5%) and the difference was statistically significant ( p < .0001); the NNT was 6.8. The standardized mean difference effect size for both PR and SA was 0.09. Conclusions: Viloxazine ER significantly reduces the impairment of PR and SA in children and adolescents with ADHD. Although its effects on PR and SA are modest, many ADHD patients can be expected to achieve clinically meaningful improvements in PR and SA with viloxazine ER treatment for longer than 6 weeks. KEY POINTS: Children and adolescents with attention‐deficit/hyperactivity disorder (ADHD) commonly experience deficits associated with peer relations (PR) and social activities (SA). Viloxazine extended‐release (viloxazine ER) is approved for the treatment of ADHD in children and adolescents. In a post hoc analysis of pooled data from four pediatric, Phase III, placebo‐controlled trials, viloxazine ER significantly improved the outcome in assessments of both PR and SA in children and adolescents with ADHD.